(untitled) (Reflection and Critique Law Magazine, 2020)
The articulation of the LGBTTT movement, and in the same way the Transgender Movement, stems from social battles fought that triggered the dissemination of collective ideas of protection, consequently in society these movements took shape and were structured to the point that they are currently inserted in transnational, being bearer of an agenda of struggles against the discriminations of such groups. The objective is to reflect on the emergence of new transsexual identities, thinking about how the international associations and networks of the Transgender Movement can contribute to the constitution of new trans identities, taking into account the local and the global, and the confrontation of discrimination against transgenders.